The evolution of the development doctrine, 1950 - 2005 - Erik Thorbecke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The evolution of the development doctrine over the last six decades is analysed in some detail in this paper. The development doctrine is defined as the body of knowledge consisting of four interrelated components: (1) the prevailing development objectives; (2) the conceptual state of the art relating to development theories, models, techniques and applications; (3) the underlying data system; and (4) the resulting development strategy. The main contributions and changes in these four components are traced through, decade by decade, starting with the 1950s.
Keywords: O10; O20; B2; 330; development; doctrine; evolution; Entwicklungstheorie